PENGUATAN SELF ESTEEM SANTRI MELALUI KOMUNIKASI INTERPERSONAL GURU BIMBINGAN KONSELING - Apriyadi, Abi (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2024)
The aim of this paper is to examine how the implementation of interpersonal communication by guidance and counseling teachers in dealing with the problems of students who experience problems of low self-esteem. The research used was descriptive qualitative by digging up information from two MTs Al-Islam Kemuja counseling guidance teachers. Data collection using interviews and observations. The results showed that counseling guidance teachers apply interpersonal communication to as an effort to deal with students' self-esteem problems. The interpersonal communication applied, by covering aspects. Openness, in this case the counseling guidance teacher applies open communication and certain strategies so that students can also open themselves to their problems for the smooth process of counseling guidance. Empathy, by showing verbal and nonverbal communication that shows the counseling guidance teacher understands the problems experienced by students. Support, providing advice and advice to problematic students. Positive feeling, giving positive messages such as motivating to be better. Equality, applying all students equally and sharing experiences if there are the same problem conditions as those experienced by counseling guidance teachers.